Analysis of the influence of the ambient temperature on the energy efficiency of solar modules by application of empirical correlations for natural convection - Shahir Fleyeh Nawaf; Mohammad Omar Salih; Younis Nather Younis (Universitas Ahmad Dahlan, 2021)
In this paper, the effect of the ambient temperature on photovoltaic (PV) modules for different angles of inclinations and different intensities of the solar radiation on the surface of PV module is considered using empirical correlations for natural convection. The analysis used an analytical model based on the energy balance equilibrium between PV module and the environment. It has been shown that in real conditions of exploitation, the value of the solar conversion coefficient of the solar energy to be determined by the manufacturer, valid for the standard test conditions (STC) for PV module (25 °C -1000 W/m2). The results obtained indicates that in the case a smaller number of PV modules corresponding to the required number for average household. The proposed procedure can be applied in the techno-economic analysis for PV system with uniaxial monitoring of the sun position as well as static PV systems.